Forgetting in early modern English literature and culture : Lethe's legacies - Ivic, Christopher, 1968-; Williams, Grant, 1965- (Routledge, 2004)
Opening up an area overlooked by Renaissance scholarship, this collection of essays historicizes and theorizes 'forgetting' in English literary texts.
Keywords: English literature -- Early modern, 1500-1700 -- History and criticism.; Memory in literature.; Mémoire dans la littérature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; English literature -- Early modern; Memory in literature; 1500-1700; Criticism, interpretation, etc.